Mobile web and intelligent information systems : 15th International Conference, MobiWIS 2018, Barcelona, Spain, August 6-8, 2018, Proceedings /: 15th International Conference, MobiWIS 2018, Barcelona, Spain, August 6-8, 2018, Proceedings. (2018) - Unknown
No abstract available